Uneven Progress in Gender Equality at Plastic Surgery Conferences: Lessons from a Decade of Meetings. Issue 3 (23rd February 2022) - Bregman, Dana E.; Ha, Grace; Tanna, Neil
Abstract : Background: The demographics of plastic surgeons and plastic surgery trainees are changing, reflecting an increase in the diversity of medical school graduates. The authors investigated the gender diversity of speakers at several plastic surgery conferences and evaluated temporal trends over a 10-year period. Methods: The following societies' conferences and years were included based on the conference agendas available for review: American Society for Aesthetic Plastic Surgery, Plastic Surgery Research Council, American Association of Plastic Surgeons, Northeastern Society of Plastic Surgeons, and American Society for Reconstructive Microsurgery. Differences in the average amount of time spoken were analyzed using an independent one-tailed t test. Results: The number of female speakers and the time allotted to speak increased for all conferences. There was not a consistent difference in the amount of time individual men and women were allotted to speak. Across the five conferences, there was no consistent relationship found between years since board certification and female participation in conference. Gender diversity among speakers at plastic surgery conferences has not kept pace with the increase in female plastic surgery trainees because those who are selected to speak are overwhelmingly men. The hypothesis that a paucity of female speakers reflects the relatively shorter duration of career experience of female plastic surgeons was not supported by these findings. Conclusion: It is imperative that conferences increase the participation of women and strive toward more accurately reflecting the burgeoning role that female surgeons have in the field at present and will have in the future.